2017
DOI: 10.3892/mmr.2017.6246
|View full text |Cite
|
Sign up to set email alerts
|

Downregulation of NPM reverses multidrug resistance in human hepatoma cells via inhibition of P-glycoprotein expression

Abstract: Multidrug resistance (MDR) is an important issue in current cancer treatments. In human cancer, drug resistance is primarily associated with the overexpression of multidrug resistance gene 1 (MDR1). Therefore, the human MDR1 gene promoter may be a target for anti‑MDR drug screening. Numerous methods to prevent MDR have been investigated. However, they have been proven to be clinically ineffective. Therefore, the aim of the present study was to investigate whether downregulation of nucleophosmin (NPM) demonstra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 51 publications
(55 reference statements)
0
6
0
Order By: Relevance
“…Nuclear factor-κB is a master regulator of inflammation [ 58 ]. Targeting NPM may provide a novel and effective method of reversing the effects of multidrug resistance, and this protein may be a potential adjuvant for tumor chemotherapy [ 59 ].…”
Section: Discussionmentioning
confidence: 99%
“…Nuclear factor-κB is a master regulator of inflammation [ 58 ]. Targeting NPM may provide a novel and effective method of reversing the effects of multidrug resistance, and this protein may be a potential adjuvant for tumor chemotherapy [ 59 ].…”
Section: Discussionmentioning
confidence: 99%
“…Initially, the activation of ABC transporter proteins was observed upon exposure to conventional chemotherapy agents such as doxorubicin, cisplatin, and 5-fluorouracil (5-FU) as their common substrates [39][40][41]. In the development of molecular therapy, sorafenib was shown to modulate multidrug resistance caused by chemotherapy.…”
Section: Drug Efflux: Abc Transporters Familymentioning
confidence: 99%
“…102 The downregulation of NPM1 expression markedly reversed the effects of multidrug resistance (MDR) in human hepatoma cells via inhibition of P-glycoprotein expression. 101 To date, relatively little is known about the role of NPM1 overexpression in hematologic malignancies. A recent study identified mutated chronic lymphocytic leukemia cells that were characterized by a MYC-related overexpression of NPM1 and ribosome-associated components.…”
Section: Npm1 Translocations In Lymphomasmentioning
confidence: 99%
“…Modulation of NPM1 expression occurred within CRC cells, affecting cellular viability, p53-dependent senescence, and cell-cycle progression, indicating that NPM1 may play a fundamental role in colorectal carcinogenesis. 97 The high expression of NPM1 has also been reported to link to gradient drug resistance in bladder cancer, 99,100 lung cancer, 15 hepatoma carcinoma, 101 and breast carcinoma. 102 The downregulation of NPM1 expression markedly reversed the effects of multidrug resistance (MDR) in human hepatoma cells via inhibition of P-glycoprotein expression.…”
Section: Npm1 Overexpression In Solid Tumors and Hematologic Malignanmentioning
confidence: 99%
See 1 more Smart Citation